RELATIONSHIP OF PARENTS EMPLOYMENT AND EDUCATION WITH NUTRITIONAL STATUS IN TODDLERS IN THE WORK AREA OF PUSKESMAS III NORTH DENPASAR - Wibawa, Anak Agung Made Adhyatmaja; Wiryanthini, Ida Ayu Dewi; Sutadarma, I Wayan Gede; Surudarma, I Wayan (E-Jurnal Medika Udayana; Vol 13 No 12 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i12.P03, 2024)
Nutritional status is a condition in which a person's nutrition can be seen to determine whether a person is normal or problematic (malnutrition). Malnutrition is a health disorder caused by a lack or excess of nutrients needed for growth, intelligence and productivity. Nutritional conditions, especially in toddlers, have an important influence on their development and growth. Various factors that influence the nutritional status of toddlers such as parental education, parental occupation, and other factors make the nutritional status of toddlers certainly different. This study aims to determine the relationship between job and parental education with nutritional status in children under five years old. This study is a descriptive analytic study with a cross sectional design using medical records. This study used a random sampling of 82 samples taken from the medical records of Puskesmas III North Denpasar. All samples were processed using the Stata application and Microsoft Excel and the results of this study showed that there was a relationship between the work of parents and the nutritional status of children under five, this was evidenced by statistical results using the chi-square test and obtained a p value of 0.000 (p<0, 05). However, there is no relationship between parental education and nutritional status in children under five, this is evidenced by the results of statistical tests using the chi-square test and the p value is 0.290 (p?0.05).